Responding to domestic violence : the integration of criminal justice and human services - Buzawa, Eva Schlesinger (Sage, 2017)
This book covers the victim's and the offender's perspective and discusses the needs, preferences and satisfaction for intervention, as well as the impact of interventions. The diversity in victims is examined, suggesting that this not only impacts their needs, preferences, and attitudes, but also differentially impacts service needs and impact of interventions. Responding to Domestic Violence provides a strong focus on the criminal justice system's responses to domestic violence and a comprehensive overview of public and non-profit social service and healthcare services and interventions. This text includes student-friendly material: end-of-chapter summaries and review questions, "Best Practices" sidebars, victim and offender case studies, and interviews with figures in the field.